Examining virtual learning environment success using DeLone and McLean IS Success Model - Awang, Hapini; Mat Aji, Zahurin; Sheik Osman, Wan Rozaini; Ishak, Mohd Sobhi (2018)
This paper examines the Virtual Learning Environment (VLE) success from the teachers’ perspective. The data analysis was done using the Partial Least SquaresStructural Equation Modeling (PLS-SEM). Due to the inability of PLS-SEM to analyze recursive relationship, the research model has been divided into Model A and Model B. All hypotheses in this study were supported. Upon the post-analysis reflection, this study seeks to find the best VLE success model that could be run on a single structural model and compensate the recursive relationships in the proposed research model. After comparing five possible models, this study found that Model 1 is the best to measure VLE success. This model suits the issue under investigation while at the same time producing good R2 and Q2 values. More importantly, without the recursive relationships, the model can be examined in a single SEM structural analysis